Analysis of The Influence of Service Quality and Brand Image in Shaping Customer Loyalty at MS Glow Aesthetic Clinic Bandung - Giana, Hasna; Apriadi, Deri (Manunggal Halim Jaya, 2025)
The influence of social media, shifting lifestyles, and increasing public awareness of appearance has contributed significantly to the rapid growth of the beauty industry. One of the beauty clinics that has successfully expanded is MS Glow Aesthetic Clinic, which offers both professional aesthetic services and premium beauty products. This study aims to examine the impact of service quality and brand image on customer loyalty at MS Glow Aesthetic Clinic Bandung. Service quality refers to the extent to which a service meets or exceeds customer expectations, while brand image represents consumers' perceptions and impressions about a brand. In this context, customer loyalty is the customer's commitment to choose MS Glow's services despite alternatives consistently. This study employs a quantitative approach, involving a survey of 30 respondents who are clients of MS Glow Aesthetic Clinic Bandung. Multiple linear regression analysis was used to evaluate both the partial and simultaneous effects of brand image and service quality on customer loyalty. The results show that service quality and brand image both positively and significantly affect customer loyalty, individually and collectively. This study is expected to contribute to academic insights in marketing, particularly in the beauty services sector, and provide practical support for MS Glow's business strategy.